A Hospital Based Prospective Randomized Double Blinded Comparative Study of Two Different Doses of Dexmedetomidine Infusion on Haemodynamic Stress Response - Mamta Damor; Amit Jain; Rinkle Sharma; Rekha Roat; Hemant Jingar (International Journal of Health and Clinical Research, 2021)
Background: Balanced anaesthesia protocols include combination of drugs of different classes used with specific purpose to create unconsciousness, muscle relaxation, analgesia and amnesia. Dexmedetomidine is a high selective centrally acting, potent alpha2 adrenergic agonist with short duration of action. The primary objective of this study was to compare the efficacy of two doses of Dexmedetomidine (0.2 and 0.4 μg/kg) as a 15 min infusion before induction for attenuating the hemodynamic stress response. Materials & Methods: This is a prospective, randomized, double blinded clinical study done on 40 patients between 18 and 55 years of age belonging to American Society of Anaesthesiology physical status 1 and 2 of either sex undergoing a variety of elective laproscopic surgeries under general anaesthesia in Government Medical College, Dungarpur, Rajasthan, during six month of period. The patients were randomly allocated into two groups of 20 patients each, Group Dex 0.2 (patients receiving Dexmeditomidine infusion 0.2 mcg/kg/h) and Group Dex 0.4 (patients receiving Dexmedetomidine infusion 0.4 mcg/kg/h). All the patients were observed for vital parameters like PR, MAP and SpO2 at regular intervals including before starting the infusion, 15 min after starting the infusion, after induction, after intubation, after creation and release of pneumoperitoneum and after extubation. Results: The results were statistically better in Dex 0.4 group compared with Dex 0.2 group. Post-operative 24 hour analgesic requirements were much less in both the groups (better effect in Dex 0.4 group). No significant side effects were noted. Conclusion: Low dose Dexmedetomidine infusion in the dose of 0.4 mcg/kg/h effectively attenuates haemodynamic stress response during laparoscopic surgery with reduction in post-operative analgesic requirements.